Experiencias emocionales frente a la vida profesional en estudiantes de último semestre del programa de enfermería (2023)
This research is carried out in order to be able to analyze the emotional experiences presented by students facing the transition to professional life of the nursing faculty of the last semesters at the Antonio Nariño Beltway University, oriented by the public health research line , coexistence and mental health, in order to be able to diagnose the experiences presented by the students, this being important from the academic field since the mission of the faculty is primary health care and research to meet the needs of the community